2022
DOI: 10.1037/hea0001142
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of presurgical Personality Assessment Inventory scales to BMI following bariatric surgery.

Abstract: Objective: Notwithstanding the efficacy of bariatric surgery in reducing the negative sequelae of obesity, psychological factors may play a significant role in long-term weight maintenance following surgery. Previous research on these factors has shown mixed outcomes, indicating the need for further study in samples undergoing bariatric surgery. Method: This study evaluated archival data for 194 patients from a single-payer system for a 60-month period following bariatric surgery to examine how presurgical sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…Our results coincide with previously published weight reduction studies. In particular, Hoyt and Walter [ 10 ] found that initial BMI was the best predictor of subsequent BMIs across time. A randomized controlled trial followed diabetic patients with OSA on dietary weight loss for 10 years [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results coincide with previously published weight reduction studies. In particular, Hoyt and Walter [ 10 ] found that initial BMI was the best predictor of subsequent BMIs across time. A randomized controlled trial followed diabetic patients with OSA on dietary weight loss for 10 years [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zusätzlich mindestens 2 Einheiten mit muskelkräftigender Bewegung (je mindesten 10 min) Reduktion der sitzenden Tätigkeiten Erhöhung der Alltagsaktivität 2.5. Psychologische Maßnahmen [ 40 ] Eingeübte Verhaltensänderungsstrategien [ 41 ] und Zielorientierung [ 42 ] evaluieren Reflexion von individuellem Emotions- und Stressmanagement [ 42 ] sowie Evaluierung der Copingstrategien (u. a. Entspannungstraining, Achtsamkeitsübungen) und der Rückfallprophylaxe Intrinsische Motivation [ 24 ], Selbstführsorge und Selbstwirksamkeit fördern und stärken Spezielle Aspekte, die bei PatientInnen nach bariatrischer Operation besonders berücksichtigt werden sollten: – Jegliche Psychopathologie kann das Outcome beeinflussen [ 43 45 ] – Abklärung der Suizidalität [ 44 , 46 48 ] – Suchtverlagerung [ 36 ], Substanzmissbrauch und selbstschädigendes Verhalten [ 43 , 46 50 ] – Förderung des positiven Einflusses von psychosozialen Interventionen [ 48 ] – Abklärung traumatischer Erlebnisse [ 25 ] – Längerfristige postoperative Begleitung begünstigt den Erhalt der Gewichtsreduktion [ 51 ] Bei Vorhandensein von psychischen Erkrankungen und/oder psychopharmakologischer Medikation empfiehlt sich bereits präinterventionell und insbesondere bei Auftreten einer postinterventionellen Gewichtszunahme und/oder Verschlechterung des psychischen Befindens eine rasche Kontaktaufnahme mit der/dem behandelnden PsychologIn und FachärztIn Exploration psychischer Befindlichkeiten und klinischer Symptome (Entwicklung von psychischen Störungen, Suchtverlagerung hin zu substanzgebundenen und -ungebundenen Süchten) [ 52 ] Auffälligkeiten im Ess- und Trinkverhalten, die eine Gewichtszunahme begünstigen, abklären und bearbeiten (u. a. Craving, Grazing, Nibbling, Loss of Control Eating, Overeating, Emotional Eating, Chewing and Spitting, Night-Eating-Syndrom) 2.6. Medizinische Maßnahmen Anpassung der Medikation an den Therapieverlauf und Begleiterkrankungen Fortführung bzw.…”
unclassified
“…Current assessment practices rely greatly on assessing psychopathology. Still, consistent evidence implicates that self-regulatory and personality processes are straightly related to obesity development and severity and might mediate the relationship between obesity and psychopathology (Claudon et al, 2012;Federico et al, 2019;Hoyt & Walter, 2022;Micanti et al, 2017;Monell et al, 2020;Parcet et al, 2020;Schäfer et al, 2017;Stapleton et al, 2020;Strimas, 2021;Wolz et al, 2015). Similarly, many studies with patients submitted to surgery provide evidence that the individuals' ability to adapt to changes after surgery and adhere to behavioral and clinical interventions are better predictors of weight-loss maintenance than specific psychopathology (Carlson, 2017;Eynde et al, 2021;Hout et al, 2005Hout et al, , 2009Raman et al, 2013;Robitzsch et al, 2020).…”
Section: Contributions Of the Multimethods Psychological Assessment T...mentioning
confidence: 99%
“…Additionally, several behavioral aspects are considered important contributors to WR, especially concerning insufficient physical activity and disordered eating behaviors. These factors are directly connected to psychological factors that increase the risk for weight recidivism, such as the presence of psychiatric disorders (Freire et al, 2021), personality features (Hoyt & Walter, 2022;Neff et al, 2021), cognitive and emotional functioning (Efferdinger et al, 2017;Manderino et al, 2015;Spitznagel, Garcia, et al, 2013;Spitznagel et al, 2014).…”
Section: Obesity Surgery: An Approach For Treatmentmentioning
confidence: 99%
See 1 more Smart Citation